Outcome of Open Pyeloplasty on Ipsilateral Renal Function (Bangladesh Journal of Urology, 2020)
Objective: The objective of this study is to determine the ipsilateral renal function after open pyeloplasty.Patients and methods: The study comprises 50 patients with ultrasonographically and urographically demonstrated hydronephrosis and primary pelvi-ureteric junction obstruction for reconstructive surgical treatment at urology department of Bangabandhu Sheikh Mujib Medical University Hospital between January 2012 and September 2013. Anderson- Hynes pyeloplasties were performed in 50 patients. Data were collected by interview, review of records and documents in data collection sheet. Data were analyzed by using paired t-test. Level of significance was set at 5%(P